EXPLORING THE IMPACT OF PLAY ON GENRE DEVELOPMENT: A SCIENTIFIC PERSPECTIVE (Academicia Globe: Inderscience Research, 2025)
Play is a fundamental aspect of human behavior that extends across various domains, including cognitive, emotional, and social dimensions. In this scientific article, we delve into the intricate relationship between play and genre development, aiming to unravel the mechanisms through which play influences the creation, evolution, and perception of different genres. By examining the cognitive and social aspects of play, we can gain valuable insights into how genres emerge, transform, and shape our cultural landscape.